Cardiac disrhytmias during ophthalmic surgeries under general anesthesia in patients with any history of heart disease - Aavani Malihe (Iran University of Medical Sciences, 1994)
The aim of this study is to find causes of cardiac disrhytmias during ophthalmic surgeries in patients under general anesthesia with no history of heart disease in Iran's educational hospitals. This was a univarient study. A sample of 250 patients selected randomly. Data were gathered by four resources: interview, patient's documents, kind of treatment selected by anesthesiologist and monitoring EKG. Data were analyzed by using χ2 and regression statistical tests. Variables such as kind of anesthetic agents, hypoxemia, cardio-ophthalmic reflex, light anesthesia presence of pain and gender, were detected on development of disrhytmias. Findings showed that kind of anesthetic agents, arterial hypoxemia, cardio-ophthalmic reflex, vague stimulation, light anesthesia and presence of pain are causes of disrhytmias. There was a significant relationship between each of these variables and presence of disrhytmias. Finding of this research and some recommendations has been reported.